Hubungan Supervisi Akademik Kepala Madrasah Dan Kompensasi Kerja Dengan Kinerja Guru Madrasah Ibtidaiyah Sekecamatan Bangorejo Kabupaten Banyuwangi - Nur Hidayati (IAI Darussalam, 2016)
This research is to (1) test the location of positive relationship and prosperity between supervision of madrasah head of madrasah with teacher performance, (2) to test the position of positive relationship and welfare between compensation work by doing performance of Islamic school teacher Ibtidaiyah Sub Bangorejo Banyuwangi, (3) positive and prosperity between supervision of madrasah head of madrasah and compensation in collaboration with work performance of Islamic school teacher ibtidaiyah sub-district Bangorejo Banyuwangi. The approach used is a quantitative approach, as correlational and in multiple linear regression. The population is all teachers' boards and a sample of 113 people. Data collected through questionnaires and data were analyzed using SPSS 15.0 for windows. The results of this study indicate that (1) madrasah head madrasah supervision has a positive and significant correlation with performance, (2) compensation work has a positive and significant relationship with performance, (3) Madrasah head madrasah supervision and cooperation compensation have a positive and significant relationship with teacher performance.